Teaching Factory Management Strategy on Light Vehicle Engineering Expertise Competency in SMK Muhammadiyah Mungkid - Yoga Hermawan; Sukirman Sukirman; Achadi Budi Santosa (Universitas Sultan Ageng Tirtayasa, 2025)
Teaching factory is a learning model that integrates theoretical and practical learning processes in schools by creating conditions that resemble the industrial world. The purpose of this study is to provide an overview of the teaching factory management strategy for light vehicle engineering expertise competencies at SMK Muhammadiyah Mungkid in improving students' competency and work readiness. This study uses a qualitative approach with a case study model with sources including the principal, vice principal for curriculum, head of teaching factory and industry partners. Data sources are taken from in-depth interviews, observations and analysis of learning administration documents. To validate the data used by comparing one source with another then comparing the results of the interview and data obtained from the results of the document review. The results of the study indicate that teaching factory management carried out with the stages of planning, organizing, implementing, effective and efficient supervision, through the integration of link and match learning involving industry partners in implementing a learning environment that is in accordance with industry standards, has been proven to improve students' competency and work readiness.